Atypical landslide induces speedup, advance, and long-term slowdown of a tidewater glacier - de Vries, Maximillian Van Wyk; Wickert, Andrew D.; MacGregor, Kelly R.; Rada Giacaman, Camilo Andres; Willis, Michael J. (My University, 2022)
Atmospheric and oceanic warming over the past century have driven rapid glacier thinning and retreat, destabilizing hillslopes and increasing the frequency of landslides. The impact of these landslides on glacier dynamics and resultant secondary landslide hazards are not fully understood. We investigated how a 262 +/- 77 x 10(6) m(3) landslide affected the flow of Amalia Glacier, Chilean Patagonia. Despite being one of the largest recorded landslides in a glaciated region, it emplaced little debris onto the glacier surface. Instead, it left a series of landslide-perpendicular ridges, landslide-parallel fractures, and an apron of ice debris-with blocks as much as 25 m across. Our observations suggest that a deep-seated failure of the mountainside impacted the glacier flank, propagating brittle deformation through the ice and emplacing the bulk of the rock mass below the glacier. The landslide triggered a brief downglacier acceleration of Amalia Glacier followed by a slowdown of as much as 60% of the pre-landslide speed and increased suspended-sediment concentrations in the fjord. These results highlight that landslides may induce widespread and long-lasting disruptions to glacier dynamics.
Keywords: Accumulation zone; Tidewater glacier cycle; Glacier mass balance; Rock glacier; Glacier morphology; Glacier terminus; Glacier ice accumulation; Cirque glacier; Submarine landslide